STRATEGI PENGEMBANGAN USAHA MIKRO DALAM MEMPERCEPAT PEMBANGUNAN KOTA PALU - Fahmi, Fahmi; Anwar, Chairil; Jokolelono, Eko (Katalogis, 2019)
The purposes of this research is (1) to know and analyse strategy of micro enterprises development in accelerating development of Palu city; (2) to know and analyze the strengths, weaknesses, opportunities and threats in the development of micro enterprises currently nature accelerate the development of the city of Palu; and (3) to know and analyze the development strategy formula that should be done by micro enterprises in accelerating the development of Palu city. This was a qualitative and quantitative research (mix methods) with 20 informants consisting of 16 businessmen in Palu, 4 employees of Cooperative Department and Micro Enterprises of Palu. Data analysis used was interactive approach and SWOT analysis. The research findings reveal that strategy form used recently for micro enterprises development in accelerating development of Palu is combination of strengths-opportunities strategies by optimizing strengths through the use of opportunities with action plan strategies as follows: (1) ease of capital access for bussiness scale development; (2) ease of access to capital for increasing market access; (3) the development of human resources to have access to new markets; (4) the development of human resources to have the potential to develop exports; (5) promotion development in order to improve market access; (6) development of business networks to protect businesses from certain types of business; (7) marketing development in order to access new markets; (8) development of partnerships to protect the business of certain types of businesses; and (9) improving access to technology throught the assistance of facilities and infrastructure development.